Research of a New Pigment Based on Copper Phthalocyanin in Paint Coating Materials - Tillaev A., Dzhalilov A.T., Yusupov M.O., Beknazarov Kh.S. (International Journal of Advanced Science and Technology, 2020)
The article analyzes the various properties of the synthesized copper, nitrogen and phosphorus-containing phthalocyanine pigments by IR spectroscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and elemental analysis. The analysis shows that the synthesized new phthalocyanine pigment contains 8.3% copper in elemental analysis, and other properties of the pigment in the paint material were also determined.